Book Review: Getting Out of Your Head, Back in Your Heart - Strong-Wilson, Teresa (Journal of the Canadian Association for Curriculum Studies, 2017)
Michele Tanaka’s book, Learning and Teaching Together: Weaving Indigenous Ways of Knowing Into Education, documents and contemplates the pedagogical effects of a unique course, Earth Fibres, designed by Lorna Williams, and guided by Indigenous elders, to immerse student teachers at the University of Victoria into Indigenous ways of knowing, by having them work with traditional Indigenous fabric and textile arts. In her book, Tanaka repeats the key questions of the course: How do you get out of your head? How do you get back into your heart? In the course, the students do this in the context of a culture that destabilizes their normative understandings of the world and of teaching, learning and the curriculum. The book uses the framework of the medicine wheel, of “walking the wheel,” and likewise, the student teachers taking the Earth Fibres course are invited on a kind of medicine walk of their own. The book contributes to efforts to Indigenize the curriculum through its thoughtful documentation of the Earth Fibres course itself, as well as the responsive, Indigenist frame in which it has been written.